2017
DOI: 10.1097/brs.0000000000002047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Iliac Screw Loosening After Adult Spinal Deformity Surgery

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 31 publications
6
49
1
1
Order By: Relevance
“…Old age, low screw density, large PI, history of revision surgery, failure to restore LL, postoperative sagittal imbalance, insufficient sacropelvic fixation, and other such factors have been reported as risk factors after sacropelvic fixation of screw loosening and pseudoarthrosis [3,[9][10][11]. Kim et al [9] reported that the rate of S1 screw loosening was 24.4% in 156 patients who underwent lumbosacral fixation for degenerative lumbar disease, and that the risk factors for screw loosening were age, poor BMD, long fusion (≥3 levels), high PI, and high mismatch of PI and LL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Old age, low screw density, large PI, history of revision surgery, failure to restore LL, postoperative sagittal imbalance, insufficient sacropelvic fixation, and other such factors have been reported as risk factors after sacropelvic fixation of screw loosening and pseudoarthrosis [3,[9][10][11]. Kim et al [9] reported that the rate of S1 screw loosening was 24.4% in 156 patients who underwent lumbosacral fixation for degenerative lumbar disease, and that the risk factors for screw loosening were age, poor BMD, long fusion (≥3 levels), high PI, and high mismatch of PI and LL.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the prevalence and risk factors for SAI screw loosening; therefore, limited information is available on this subject. The risk factors for distal junctional failure after long instrument fusion using iliac screws include advanced age, low screw density, large pelvic incidence (PI), revision surgery, failure to restore lumbar lordosis (LL), postoperative sagittal imbalance, and insufficient sacropelvic fixation [3,[9][10][11]. However, it is unclear whether these risk factors are associated with SAI screw loosening.…”
Section: Introductionmentioning
confidence: 99%
“…In our results, no loosening occurred in the nine repositioned screws. Banno et al 1) reported that the loosening group had a significantly higher rate of misplacement than the non-loosening group (54.5% vs. 16.0%). However, in our results, only one lateral wall violation occurred in 15 loosened screws, and no loosening occurred in the other misplaced screws.…”
Section: Discussionmentioning
confidence: 99%
“…The surgeons should keep in mind that inferior wall or lateral wall perforation of iliac screw leads to postoperative pain that could require revision surgery. Screw loosening, represented as a radiolucent area around the screw, indicates loss of screw fixation and potential progression to pseudarthrosis 1,17) . The prevalence of iliac screw loosening after long spinal fusion is known to be particularly high (7.5-52%) 3,11,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Тактика лечения рассматриваемой патологии не имеет общего шаблона, поскольку зависит не только от особенностей заболевания позвоночника, но и от ряда индивидуальных факторов, присутствующих у конкретного пациента. В случае выбора хирургического метода лечения, некоторыми авторами предлагается вовсе избегать инструментальной фиксации при лечении пациентов с сопутствующим остеопорозом [9,10,11]. Однако критиче-ские формы дегенеративного сколиоза с выраженной полисегментарной симптоматикой являются показанием для реконструктивных хирургических вмешательств с необходимостью имплантации металлоконструкции, стабилизирующей позвоночник.…”
Section: вопросы вертебрологииunclassified